Effect of Omega-3 Supplementation on Psoriasis Severity: An Evidence-Based Case Report - Basalamah, Tarafainy; Nurul Ratna Mutu Manikam (Fakultas Kedokteran, Universitas Andalas, 2025)
Background: Psoriasis is a chronic inflammatory skin disorder often associated with significant morbidity and limited efficacy of conventional treatments, which may also cause adverse effects. Omega-3, with their anti-inflammatory and immunomodulatory properties, have been proposed as a potential adjunctive therapy for managing psoriasis. This evidence-based case report (EBCR) aims to evaluate the efficacy of omega-3 supplementation in improving clinical outcomes in patients with psoriasis. Objective: To determine the effect of omega-3 supplementation on changes in Psoriasis Area and Severity Index (PASI) scores in psoriasis patients. Methods: Literature search was conducted using advanced searching in three large databases: PubMed, Cochrane Library, and ProQuest. MeSH terms, advanced search and eligibility criteria were used for title and abstract screening after removing duplicates. Critical assessment tools and levels of evidence of the final articles are based on the Oxford Center for Evidence-Based Medicine. Results: Three systematic reviews and meta-analyses and one RCTs met the PICO and eligibility criteria that had been set. Three of the studies demonstrated a modest but statistically significant reduction in PASI scores with omega-3 PUFA supplementation, particularly when combined with conventional therapies. A study showed limited or non-significant effects when omega-3 was used alone. Conclusion: Omega-3 supplementation demonstrates a beneficial effect in reducing disease severity in patients with psoriasis, as evidenced by improvements in PASI scores.